Sensitivity Study of Hybrid Photovoltaic/Diesel Energy System in Nigeria - Emmanuel Chinweikpe Obuah; Ikpe Chikwe Okora (Journal of Power Electronics and Devices, 2020)
Energy supply is a prerequisite for enhancing industrial development in every nation. Unreliable power supply which is peculiar to many developing nations particularly the sub-Sahara African countries has been reported to be grossly responsible for the poor growth industries. Hybrid energy system which combines two or more than two energy conversion devices or two or more than two fuels for generation of power has been used in different regions to enhance the sustainability of electricity supply. This paper presents a hybrid Photovoltaic/diesel energy system configured to serve a peak load (AC) of 18kW. With fuel price displaying an upward trend in recent time, it is expected that price increases would occur during the project lifetime. The then paper focuses on sensitivity analysis of hybrid PV/diesel energy system for an oil and gas industries in Nigeria. The research considered six cases of 0.1 per liter fuel pump price increment for 20 years project life time each. The study was successful using HOMER software based on total net present cost (NPC). With other sensitivity variables such as solar irradiation set at 5380Wh/m2/day and battery state of charge set at 100% and solar Photovoltaic (PV) slope angle set at 10o, it was deduced that as the fuel pump price increases the total NPC increases as well. 7% incensement of the total NPC was obtained on the six cases from the initial total NPC obtained in the first case. The study is performed in a special region in South-West of Nigeria and can be beneficial to power operators in terms of energy planning and cost forecasting.